The Development of Android-Based Mobile Learning (M-Learning) on Voltaic Cell Sub Materials to Increase Learning Effectiveness in Pandemic Covid-19 Era - Dei Gratia Kanthi Nabella; Kusumawati Dwiningsih (Jurnal Penelitian Pendidikan IPA, 2022)
This study was conducted to know the worthiness of learning media mobile learning (M-Learning) is increasing students' learning effectiveness. Research and Development (R&D) has adapted the method used. The research was conducted involving 26 students and three validators. The validator consists of 1 lecturer as a media expert lecturer, one material expert, and one chemistry teacher. Based on the study results, the results obtained media validity of 93%, and the effectiveness of the media in terms of increasing student scores as much as 41.9%. So that the android-based M-Learning product developed can be said to be feasible and can be implemented in chemistry learning on voltaic cell sub materials.